1991
DOI: 10.1093/clinchem/37.8.1436
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage time and temperature on urinary enzymes

Abstract: We measured three renal tubular brush-border enzymes (lactate dehydrogenase, LDH, EC 1.1.1.27; gamma-glutamyltransferase, GGT, EC 2.3.2.2; and alkaline phosphatase, AP, EC 3.1.3.1) in morning urine samples from 48 healthy subjects to check whether different storage times and temperatures could modify enzyme concentrations. Short-term (24 h) storage time at room temperature or 4 degree C does not affect urinary enzyme activity. A few days of freezing, at -20 or -70 degrees C, dramatically lowers LDH and AP valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…At −80°C, enzyme activity was somewhat preserved, although urine GGT activity did start to decline following 14 d of storage. These findings are similar to those reported in human samples, 11 and support the guidance that urine intended for GGT activity studies must not be frozen.…”
Section: Discussionsupporting
confidence: 88%
“…At −80°C, enzyme activity was somewhat preserved, although urine GGT activity did start to decline following 14 d of storage. These findings are similar to those reported in human samples, 11 and support the guidance that urine intended for GGT activity studies must not be frozen.…”
Section: Discussionsupporting
confidence: 88%
“…Freezing results in significant reductions in urinary AAP activity, whereas it exerts only a minor effect on the enzyme activity in Sephadexfiltered urine samples (Sephadex G-25 M, Amersham Pharmacia Biotech AB, Upsala, Sweden) (E. Taracha, unpublished data). Similar observations have been reported for other enzymes (Mattenheimer and Maruhn, 1992;Matteucci and Giampietro, 1994;Matteucci et al, 1991). Therefore, in this study urine samples were kept refrigerated at ϩ4°C (for no longer than 3 days) until assayed for AAP activity.…”
Section: Biochemistrysupporting
confidence: 80%
“…Research has suggested urine samples should not be frozen for albumin determination and refrigeration does not appear to be necessary ( 11 , 13 ). When samples are stored for 24 hours, storage at room temperature or 4°C does not appear to effect urine enzyme values ( 14 ). Similar to the literature, our findings suggested samples do not need to be refrigerated or frozen if assessed within 48 hours of voiding.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, limited research is available investigating the effect storage temperature has on urine specimen, none of which concentrates on hydration status. Studies that focused on the impact of storage temperature on albumin determination and urine enzyme values have suggested urine samples should not be frozen and can be stored for 24 hours at room temperature or 4°C without impacting results ( 11 - 14 ).…”
Section: Introductionmentioning
confidence: 99%